Soil Fungus and Bacteria Antagonism Test to Control Phytophthora nicotianae in The In Vitro - Istifada, Valia; Syib’li, Muhammad Akhid; Sektiono, Antok Wahyu; Ratdiana, Ratdiana; Limin, Atfritedy (Journal of Tropical Plant Protection, 2022)
This study aims to determine the potential of antagonistic fungi and bacteria as controlling agents for Phytophthora nicotianae. The research was conducted at the Laboratory of Biological Control 1, Department of Plant Pests and Diseases, Faculty of Agriculture, Universitas Brawijaya, Malang. The method used is soil sampling, isolation, purification, identification and in vitro antagonism test. The antagonism test is done by the dual culture method. This study used a completely randomized design for eight treatments, including the control and each treatment was repeated four times. In this study, the antagonism test results were obtained between antagonistic fungi and Phytophthora nicotianae, which Penicillium sp. (PEG01) had the highest percentage of inhibition, and the one with the lowest total diameter was Trichoderma sp. (TRC01). Moreover, the antagonism test results were obtained between antagonistic bacteria and Phytophthora nicotianae, which bacteria C had the highest percentage of inhibition and the lowest total diameter.